Autonomous Integrated Microfluidic Circuits for Chip‐Level Flow Control Utilizing Chemofluidic Transistors. (14th June 2017) - Frank, Philipp; Gräfe, David; Probst, Christopher; Haefner, Sebastian; Elstner, Martin; Appelhans, Dietmar; Kohlheyer, Dietrich; Voit, Brigitte; Richter, Andreas
Abstract : In microfluidics, a variety of platforms have emerged facilitating various physical effects for manipulating small volumes. Despite great functional diversity, most technologies are incapable of acting on direct feedback from the process liquid and instead require a sophisticated external control unit off‐chip. Here, a microfluidic platform concept is demonstrated utilizing the volume phase transition of polymers via transistor‐like components to actively switch between discrete fluid streams. Control is integrated at chip level for the first time, relying on information carried within the process liquid. Control commands are chemical signals such as solvent concentration, pH‐value, or even salt. The developed logical modules can be interconnected independently through conclusive signal propagation, supporting an integrated circuit concept and large‐scale integration. The approach enables the development of the basic logic gates (AND, OR, NOT) and their negated counterparts, as well as more sophisticated circuits such as an RS flip‐flop and a chemofluidic oscillator. Abstract : Microfluidic integrated circuits (ICs) based on stimuli‐responsive hydrogels utilize chemical information in form of molecule concentration for flow control. The circuit concept in combination with a chemofluidic transistor‐like device facilitates a vivid analogy to electronics. The implementation of a series of basic circuits such as logic gates, an RS flip‐flop, an oscillator circuit, and a first application in single‐cell analysis are demonstrated.